Digital addiction and relationship between fomo, personality factors and happiness: an application in university students - Sarıca Keçeci, Hande; Kâhya Özyirmidokuz, Esra; Özbakır, Lale (Journal of Dependence, 2021)
Objective: This research explores the relationships between social media addiction, smartphone addiction, gaming disorder and personality, fear of missing out on developments (FoMo) and happiness.Method: This study was conducted with 497 volunteer participants (61,2% female, 38,8% male) who were Erciyes University students. The questionnaire consists of Five- Factor Personality Scale, Uskudar Fear of Missing Out Scale, Smartphone Addiction Scale (SAS), Internet Gaming Disorder Scale (IGDS9-SF), Social Media Addiction Scale (SMAS-SF), Toronto Alexithymia Scale and Oxford Happiness Scale.Results: There is a significant correlation between mobile addiction, gaming disorder, FoMo and social media addiction Neuroticism, agreeableness and conscientiousness with mobile addiction were correlated with gaming disorder. Significant relationships were found between social media addiction and neuroticism; virtual communication and virtual problem with conscientiousness and also between virtual knowledge and extraversion. Conclusion: It was determined there are prominent relationships between factors of social media addiction, smartphone addiction, game-playing disorder, personality traits, fear of missing out (FoMo) and happiness.
Keywords: Digital addiction; personality; fear of missing out; happiness